2021
DOI: 10.1002/joc.7170
|View full text |Cite
|
Sign up to set email alerts
|

Divergent changes of the elevational synchronicity in vegetation spring phenology in North China from 2001 to 2017 in connection with variations in chilling

Abstract: Mountain ecosystems are sensitive to climate change, and vegetation phenology provides one of the best signals to exemplify ecosystem responses to climate change. Vegetation phenology of mountain ecosystems is usually characterized with an elevational pattern, with the growing season starts earlier and ends later in lower versus higher elevations. With climate change, this elevational gradient of vegetation phenology is likely to shift as well. However, both the patterns and the underlying driving forces for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Changes in these two factors have been widely used to explain the phenological changes of trees in response to increasing temperature [ 33–36 ]. A warmer spring advances growth reactivation in both primary meristems (buds and leaves) and secondary meristems (cambium) [ 28 , 35 ]. However, warmer conditions reduce chilling accumulation in autumn and winter, and delay spring phenology, mainly by increasing the heat requirement [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these two factors have been widely used to explain the phenological changes of trees in response to increasing temperature [ 33–36 ]. A warmer spring advances growth reactivation in both primary meristems (buds and leaves) and secondary meristems (cambium) [ 28 , 35 ]. However, warmer conditions reduce chilling accumulation in autumn and winter, and delay spring phenology, mainly by increasing the heat requirement [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past 40 years, vegetation phenology in China has made great progress. However, despite many investigations on the response of vegetation phenology to climate change (Chen and Xu, 2012; Dai et al, 2021; Wang et al, 2015b), there are still relatively few studies focusing on the ecological and climatic feedbacks of vegetation phenology. In addition to research on the spatiotemporal characteristics and trends of phenology, there are more areas where phenological research could be applied.…”
Section: Prospects For Vegetation Phenology Researchmentioning
confidence: 99%
“…The changes of heat accumulation and chilling in latitude and altitude gradient will also have different effects on spring phenology (Hänninen, 2016). Dai et al (2021) demonstrated that the chilling change related to altitude is the main reason for the significant reduction of altitude sensitivity of SOS in temperate mountains. Warming, especially at night-time, reduces the preseason chilling in low-latitude and low-altitude areas and delays SOS (Fu et al, 2015), but warming in high-latitude and highaltitude areas will increase the chilling and promote the advance of spring phenology (Güsewell et al, 2017).…”
Section: The Effects Of Diurnal Warming On Spring Phenologymentioning
confidence: 99%